A comparison of manual versus hydrostatic reduction in children with intussusception: Single-center experience - Servet Ocal; Muazez Cevik; Mehmet Emin Boleken; Ekrem Karakas (Wolters Kluwer Medknow Publications, 2014)
Objective: In recent years several techniques have been recommended for intussusception treatment. In this study, an evaluation was made of intussusception cases that presented at our clinic and had reduction applied together with saline under ultrasonography (USG) and cases, which were surgically treated. Patients and Methods: A retrospective evaluation was made of the records of 72 cases treated for a diagnosis of intussusception between January 2010 and July 2012. Patients were evaluated demographics, clinical presentation, management strategy, during the hospitalisation and outcome. Results: A total of 72 cases which consists of 44 male and 28 female with age range between 5 and 132 months were treated with a diagnosis of intussusception. USG was applied to all cases on initial presentation. As treatment, hydrostatic reduction (HR) together with USG was applied to 47 cases. Of these, the HR was unsuccessful in 13 cases. Surgical treatment was applied to 38 cases. Of these cases, ileocolic intussusception was observed in 30 cases, ileoileal in seven cases and colocolic in one case. Meckel diverticulum was determined in five of these cases, polyps in two cases, lymphoma in two cases, lymph nodule in one case and 28 cases were observed to be idiopathic. There was no mortality in any case. Conclusion: HR together with USG is a safe technique in the treatment of intussusception, which also shortens the duration of hospitalisation and significantly reduces the treatment costs.